Du Pont System Analysis In Financial Performance Of Bumn Banking Companies Listed On The Indonesian Stock Exchange In 2018-2022 - Muhamad Ripai; Nurul Syifa Qur’aini; Widi Pramesia Utami; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
This study aims to measure the financial performance of state-owned banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period with the Du Pont System analysis, the results of this study indicate that the company PT Bank Negara Indonesia (Persero) Tbk average value of 8.448% smaller than 8.877% is categorized as performing less well, PT Bank Rakyat Indonesia (Persero) Tbk average value of 9.760% greater than 8.877% is categorized as performing well, PT Bank Tabungan Negara (Persero) Tbk average value of 6.562% less than 8.877% is categorized as performing less well, PT Bank Mandiri (Persero) Tbk average value102.739% greater than 8.877% is categorized as performing well. By using Du Pont System analysis, Return on Investment (ROI) and Return on Equity (ROE) in Time Series fluctuates in increase and decrease. By using the Du Pont System analysis on a Cross Sectional basis in BUMN Banking companies listed on the Indonesia Stock Exchange for the 2018-2022 Period, an average value of 8.877% was obtained. This shows that overall financial performance is said to be performing "GOOD".